Role of NT-proBNP Level in Heart Failure in Children: A Review (Dhaka Shishu (Children) Hospital Journal, 2025)
Paediatric heart failure is associated with significant morbidity and mortality. In adult heart failure patients, the role of cardiac biomarkers has exponentially increased over the last two decades. There is enough evidence to support the use of cardiac biomarkers as an adjunctive marker in the integrated evaluation of patients with congenital and acquired heart disease to define severity and progression of heart failure as well in the monitoring of response to treatment. Cardiac biomarkers can also be used for the screening of heart failure and as a prognostic marker in children undergoing cardiac surgery. Of all the biomarkers, BNP continues to be the dominant biomarker even in pediatric heart failure. Although B-type Natriuretic Peptide (BNP), N-terminal-proBNP (NT-proBNP), and mid-regional-proANP (MR-proANP) are included in current guidelines on heart failure in adults, no guideline considering these biomarkers in pediatric heart failure is available.DS (Child) H J 2023; 39(2): 115-119